The Role of Transfer Pricing, Financial Distress, Business Strategy and Institutional Ownership on Tax Avoidance - Desi Jelanti; Muhammad Angga Wiajaya; Amanda Mardhiatul Maul (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to examine the effect of transfer pricing, financial distress, business strategy and institutional ownership on tax avoidance. This study uses a quantitative approach and uses an associative method. The type of data used in this study is secondary data. The data analysis method used in this study is Panel Data Regression Analysis using the Eviews version 10 application and Microsoft Excel. The population used in this study were companies included in the LQ45 Index with a research period of 2018-2023. The sampling technique used the purposive sampling method with 45 Company populations becoming 9 final research samples processed in this study. The results of the study show that simultaneously transfer pricing, financial distress, business strategy and institutional ownership have an effect on tax avoidance. Partially transfer pricing has an effect on tax avoidance, while financial distress, business strategy and institutional ownership have no effect on tax avoidance